Shadow of vengeance [videorecording (DVD)] - Diamond, Rob, 1965-; Boone, Derek; Diamond, Scarlett; Mulroney, Ken; Stewart, Cari, (Actor) (Deskpop Entertainment, 2024)
A Former Navy Seal and Medal of Honor recipient faces his darkest battle when the man who killed his mother is freed, and his niece is brutally attacked. Fueled by vengeance, he takes justice into his own hands.